FUNGSI KOMUNIKASI ORGANISASI PT ACCELIST LENTERA INDONESIA DALAM IMPLEMENTASI WORK FROM ANYWHERE (WFA) - Novita Resti Aprianti; Liliyana; Fajar Muhamam (Journal of Research and Publication Innovation, 2025)
With the COVID-19 pandemic, companies in Indonesia are required by the government to limit people from leaving the house. The existence of these rules PT Accelist Lentera Indonesia Implements Work at home. PT Accelist Lentera Indonesia itself is an IT company engaged in technology. the purpose of this study is to analyze the organizational communication function of PT Accelist Lentera Indonesia in implementing the Work from Anywhere (WFA) policy. This research uses a qualitative method with a case study approach to explore how organizational communication supports the implementation of WFA. Data was collected through interviews, observations, and document analysis. The results show that effective communication plays a crucial role in maintaining employee productivity and engagement while working remotely. The findings are expected to provide insights for other companies implementing WFA policies as well as enrich the literature on organizational communication in flexible working contexts.